Effect of coating maize seed with entomopathogenic fungi on plant growth and resistance against Fusarium graminearum and Costelytra giveni. Issue 9 (2nd September 2019) - Rivas-Franco, Federico; Hampton, John G.; Morán-Diez, Maria E.; Narciso, Josefina; Rostás, Michael; Wessman, Per; Jackson, Trevor A.; Glare, Travis R.
ABSTRACT: Some entomopathogenic fungi such as Metarhizium and Beauveria not only have the ability to infect and kill insects but also the capability to associate with plant roots. The potential benefits from this plant-fungus association include nutrient acquisition, plant growth promotion and protection against stressors. The objective of this study was to evaluate the delivery of entomopathogenic fungi in seed coating to determine whether the fungal presence affected maize performance. Additionally, fungal biocontrol ability was assessed in terms of plant resistance to the larvae of Costelytra giveni (Coleoptera: Scarabaeidae) and to the fungus Fusarium graminearum (Nectriaceae). Maize seeds were coated with conidia from Metarhizium spp. or Beauveria bassiana and plant performance was evaluated as seed germination and plant dry weight. Larval mortality and the presence of Fusarium root rot symptoms were also determined. The entomopathogenic fungal persistence on the maize rhizosphere was demonstrated with a M. anisopliae isolate expressing the green fluorescent protein. Presence of both challengers was detrimental to maize performance with 33% reduction in root dry weight in control plants while no variation was observed when the entomopathogenic fungi were used to coat seeds. Some seed coatings resulted in up to 67% mycosis of C. giveni larvae and a reduction in Fusarium rot root symptoms between 24 – 44%. This study showed that seed coating with conidia of Metarhizium or Beauveria can be used as a delivery system for pests and plant pathogen control, while at the same time hyphae formed a close association with plant roots after conidial germination.